Methods and technologies supporting information and knowledge management on the example of the police - Agnieszka Szczygielska (Foundations of Management, 2014)
This work refers to one of the hierarchical organizations, which is the police. The example of the Municipal Crowd Management (Sto±eczne Stanowisko Kierowania; SSK) has been chosen as the basis for a detailed analysis presented in this article. The Department, as the place where the work of many individuals, departments and services is integrated, must demonstrate a high level of knowledge, competence, and coordination activities. The innovative technologies appear to be the unquestionable support. They should primarily serve the needs of managing knowledge on the efficient actions in relation to the socio- market requirements. In case of this organization, these solutions play a vital part in the creation of intelligent organization to support its activities focused on delivering effective public services and thus contributing to build the knowledge economy in Poland. An attempt to present the discussed issues has been taken in this study.
Keywords: 650; hierarchical organizations; knowledge management; high-technology; the police; police management